x → − 1 lim x 2 − ∣ x ∣ cos 2 − cos ( 2 x ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
x → − 1 lim x 2 − ∣ x ∣ cos 2 − cos 2 x
Using cos 2 x identity,
x → − 1 lim x 2 − ∣ x ∣ cos 2 + sin 2 x − cos 2 x
Applying L'Hôpital's rule and using ( u 2 ) ′ = 2 u u ′ ,
x → − 1 lim 2 x − ∣ x ∣ x 0 + ( 2 sin x cos x ) − ( 2 ( − sin x ) cos x )
Using 2 sin x cos x identity,
x → − 1 lim 2 x − ∣ x ∣ x 2 sin 2 x
Substituting x by -1.
x → − 1 lim ( − 2 sin ( − 2 ) )
≈ 1 . 8 1 8
There's an easier to solve this. Can you find it?
@Vaibhav Prasad @Kalash Verma want to share your methods?
Problem Loading...
Note Loading...
Set Loading...
x → − 1 lim x 2 − ∣ x ∣ cos 2 − cos 2 x As when x < 0 , ∣ x ∣ = − x , x → − 1 lim x 2 + x cos 2 − cos 2 x Applying L'Hópital Rule, x → − 1 lim 2 x + 1 2 sin 2 x 2 sin 2